Actividad física y calidad de vida en los estudiantes de la Carrera De Educación Básica de la Universidad Nacional de Loja - Jaramillo Sarango, Karla Andreina (2024)
This research focuses on my perspective as a physical education professional regarding the importance of physical activity and its benefits in contributing to good health and an improved quality of life. University life represents a crucial period in the personal and academic development of young people, marked by significant changes in their lifestyle. In this context, physical activity emerges as a fundamental factor that not only influences physical health but also profoundly impacts the quality of life of students. The aim of the research is to propose a health improvement plan for students, providing information that can contribute to the promotion of healthy habits. It is expected to demonstrate how the incorporation of physical activity can transform the university experience, benefiting not only academic performance but also the emotional and social well-being of students. The research includes a survey directed at students in basic education to explore their ideas and experiences related to physical activity and quality of life. The results indicate that a significant majority (78%) of basic education students lack good physical activity habits, both in their university life and in their jobs and leisure time. This suggests that physical activity is not a priority for most of them. In contrast, only 12% engage in physical efforts, indicating that it is a minority who maintain an active lifestyle. Additionally, a series of conclusions are presented; the lack of response from 9% of students may indicate a lack of awareness about the importance of physical activity, as well as a possible disconnect from their own well-being. Keywords: Physical activity; Quality of life; Basic education students; Health; Lifestyle.